Improving English as a Foreign Langugae (EFL) Students’ Motivation in Blended Learning - Siregar, Dio Ilham Prasetyo; Triastuti, Anita (Formosa Journal of Sustainable Research, 2025)
Siregar, Dio Ilham Prasetyo. Improving English as a Foreign Language (EFL) Students’ Motivation in Blended Learning. Thesis. Yogyakarta. Faculty of Language, Art and Cultures, Yogyakarta State University. This study aims: (1) examine how blended learning is being used in teaching writing of EFL Hamong Putera junior high school setting. (2) to determine the ways in which blended learning can raise students’ motivation in teaching writing of EFL Hamong Putera junior high school. The research design includes 2 cycles, each comprising four phases: planning, acting, observing, and reflecting. The study involved 18 ninth-grade students over 2 cycles. Data collection methods included observations, interviews, and questionnaires, with data analyzed using a quantitative descriptive approach. The qualitative findings from observations and interviews revealed significant improvements in EFL student motivation within a blended learning environment